THE FUNCTIONS OF ILLOCUTIONARY ACTS IN FINDING NEMO FILM - Lisa Aprilia; Eti Kusmala Dewi (Universitas Muhammadiyah Lampung, 2022)
This research focuses on analyzing illocutionary acts in Finding Nemo film. This research uses speech acts theory of pragmatics approach to analyze the meaning of illocutionary acts uttered in the film. This research applies qualitative method. The functions of illocutionary act uttered by the characters in Finding Nemo are declarative, representative, expressive, directive, and commisive. The functions of illocutinary acts in the film are classified on theory of Yule, Word Orders and Performative Verbs as the indicator.